Analisis Pengaruh ROA, Ekuitas dan Inflasi Terhadap Pendapatan dengan Pembiayaan Musyarakah sebagai Variabel Intervening pada Bank Mega Syariah di Masa Pandemi - Budianto, Achyat; Ferawati, Rofiqoh; Prayogo, Youdhi (Jurnal Ilmiah Wahana Akuntansi, 2023)
This study aims to determine the effect of ROA, equity, and inflation on income with Musyarakah financing as an intervening variable at Bank Mega Syariah during the pandemic. The sample in this study comes from the financial reports of Bank Mega Syariah for the period 2020–2022. The data in this study are secondary data, totaling 35 data points. Hypothesis testing uses path analysis with the help of the Eviews program. The research results show that the musyarakah financing variable is able to mediate the effect equity has on income, while ROA and inflation have no effect on income through musyarakah financing. During the pandemic, the study aims to determine the effect of ROA, equity, and inflation on income with Musyarakah financing as an intervening variable at Bank Mega Syariah. The sample in this study comes from the financial reports of Bank Mega Syariah for the period 2020–2022. The data in this study are secondary data, totaling 35 data points. Hypothesis testing uses path analysis with the help of the Eviews program. The research results show that the musyarakah financing variable is able to mediate the effect equity has on income, while ROA and inflation have no effect on income through musyarakah